The concept of international responsibility arising from the phenomenon of climate change, its types, and its legal effects - Emad Sahib Al- Mutar, Researcher. Hassan; Jabbar Creedy Al-Qadi, Prof. Dr. Ali (Basra studies journal, 2024)
The flexibility of the rules of environmental law in general, and climate law in particular, has made it easier for states and other public international persons, as well as private international persons, to violate them in a way that makes it difficult to ascertain the perpetrator of that violation, and to evade its consequences, and the various harms that result from it to individuals. property, and the environment in general, those illegal violations that took the form of international and internal environmental, climatic, and internal crimes punishable by international and national laws as well, and holding the perpetrators responsible, whether civil liability depends on compensation, restoring the situation to what it was or penal responsibility that has become Its provisions and rules are applied without discrimination to the natural person and the legal person together according to legal procedures stipulated by internal laws or public international law.